CASSINI-HUYGENS: The Space Probe That Changed Saturn’s and Its Icy Moons Titan and Enceladus Comprehension - Henrique Martins, Fernando; Leonardo Ferreira, José (Instituto de Física - UnB, 2023)
This year, the Cassini-Huygens mission completes five years since its demise when it was purposely launched to crash into the thick atmosphere of our great “Lord of the Rings”. For almost twenty years, this mission has obtained surprising results on the complex Saturn system, revealing mysteries and obscured phenomena due to the enormous distance that separates this planet from Earth. In this context, the main achievements of the Cassini mission sent to investigate Saturn, its rings and moons will be presented, emphasizing the results obtained on the moons Titan and Enceladus from an extensive literature review. The equipment and experiments that traveled aboard the Cassini spacecraft and the European probe Huygens collected data and revealed jet streams in Saturn’s atmosphere, long storms that sweep the planet from east to west, and aurora borealis phenomena occurring on its upper atmosphere. In addition, the mission contributed to a better understanding of the interactions that exist between Saturn, its rings and its moons. Finally, the Cassini spacecraft revealed that the icy moon Enceladus presents geological activity such as cryovolcanism and Titan has lakes, rivers and oceans of hydrocarbons that undergo transformations similar to those that water undergoes here on Earth. Neste ano, a missão Cassini-Huygens completa cinco anos desde seu desfecho quando foi lançada propositalmente para colidir contra a espessa atmosfera do nosso grandioso “Senhor dos Anéis”. Durante quase vinte anos, esta missão obteve surpreendentes resultados sobre o complexo sistema saturnino revelando mistérios e fenômenos obscurecidos pela enorme distância que separa este planeta da Terra. Nesse contexto, serão apresentados os principais feitos da missão Cassini enviada para investigar Saturno, seus anéis e suas luas dando ênfase aos resultados obtidos sobre as luas Titã e Encélado a partir de uma extensa revisão bibliográfica. Os equipamentos e experimentos que viajaram a bordo da espaçonave Cassini e da sonda europeia Huygens ...